Educational video for teaching safe practices in the perioperative period: randomized controlled trial - Raissa Bianca Luiz; Maria Beatriz Guimarães Raponi; Patrícia da Silva Pires; Maria Sagrario Goméz Cantarino; Maria Helena Barbosa (Universidade de São Paulo, 2024)
Objective: to assess the effectiveness of an educational video on hospitalized patients' knowledge of safe practices in the perioperative period. Method: randomized, double-blind controlled trial carried out in a teaching hospital in the countryside of Minas Gerais. 100 participants undergoing elective orthopaedic surgery were randomly allocated (50 participants in the experimental group and 50 participants in the control group). Patient knowledge was assessed using a questionnaire constructed by the researchers and validated by specialists, before and after the intervention (educational video) or standard guidelines were applied. Descriptive statistics were used for quantitative variables and Student's t-test for independent samples to analyze the mean difference in knowledge between the experimental and control groups (α = 0.05). Results: 100 participants took part in the study, 50 participants in the experimental group and 50 participants in the control group. The experimental group showed a significantly higher gain in knowledge (t =3.72 ±1.84; p<0.001) than the control group. Cohen's d was 1.22, indicating a large magnitude of the effect. Conclusion: the educational video was effective in improving patients' knowledge and can contribute to nurses in the practice of health education, optimizing time and disseminating knowledge about safe practices in the perioperative period. Brazilian Registry of Clinical Trials (REBEC): RBR-8x5mfq.